Efektivitas Implementasi LKPD Bahasa Indonesia Berbasis Kearifan Lokal Sedekah Bumi bagi Peningkatan Kompetensi Berbahasa Siswa Kelas V - Istiq’faroh, Nurul; Mufida, Firyal Amelia; Iskandari, Neila Aulya (CV. Kurnia Grup, 2026)
This study is motivated by the low effectiveness of Indonesian language learning in elementary schools, which is still dominated by conventional teaching methods and lacks connection to students’ real-life contexts. This condition affects students’ engagement, learning independence, and overall achievement. Therefore, this study aims to analyze the effectiveness of implementing student worksheets (LKPD) based on the local wisdom of Sedekah Bumi in improving fifth-grade students’ language competencies. This research employed a quantitative approach with a pre-experimental design using the One Group Pretest–Posttest Design. The subjects of this study were 19 fifth-grade students of SDN Karangpuri 2. Data were collected through pretest and posttest, as well as student response questionnaires. The data were analyzed using descriptive statistics, normality test, paired sample t-test, and N-Gain test. The results showed a significant improvement between pretest and posttest scores, with a significance value of 0.000 < 0.05. The average N-Gain score was 0.5444, which falls into the moderate category, indicating that the use of LKPD based on local wisdom is sufficiently effective in improving students’ learning outcomes. In addition, the language aspect achieved a very good category, while the structure, content, and effectiveness aspects were categorized as good. The integration of local wisdom into LKPD creates contextual learning, increases student motivation, and facilitates understanding of the material. Thus, LKPD based on local wisdom is proven to be an effective innovation in Indonesian language learning at the elementary school level.